Kinerja Guru Bimbingan dan Konseling Dalam Menghadapi Perubahan Kurikulum - Nikmah Ranti Maulidah; Tri Yuni Hendrowati; Siswoyo (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the performance of Guidance and Counseling teachers in facing the dynamics of curriculum change. This study focuses on analyzing the strengths and opportunities, weaknesses and threats, and strategies of Guidance and Counseling teacher performance in facing curriculum change. The research approach used is qualitative with descriptive methods. The subjects of this study were three Guidance and Counseling teachers of junior high schools in Tanggamus who were selected through purposive sampling techniques. Data were obtained through observation, structured interviews, and documentation which were analyzed using triangulation techniques to increase validity. The results of the study indicate that Guidance and Counseling teachers have strengths and opportunities to face weaknesses and threats, as well as strategies in optimizing the performance of Guidance and Counseling teachers in facing curriculum change. The strengths and opportunities of Guidance and Counseling teachers include: 4 competencies of Guidance and Counseling teachers, as well as stakeholder support, available infrastructure, peer support, and student perceptions of Guidance and Counseling. Meanwhile, the weaknesses and threats are inability in time management, lack of focus, not yet optimal in archiving, leaders who do not understand BK, facilities and infrastructure, various student problems, and changes in government policy. The strategy is that Guidance and Counseling teachers are able to: (1) utilize existing strengths and opportunities, (2) overcome weaknesses by utilizing existing opportunities, (3) utilize strengths to face threats, and (4) minimize weaknesses to face threats. This study contributes to the development of using SWOT analysis in analyzing supporting and inhibiting factors in the performance of Guidance and Counseling teachers which will be a guideline in determining strategies so that the performance of Guidance and Counseling teachers in facing curriculum changes can run optimally.